Early Antiretroviral Therapy Is Protective Against Epilepsy in Children With Human Immunodeficiency Virus Infection in Botswana. (1st June 2015) - Bearden, David; Steenhoff, Andrew P.; Dlugos, Dennis J.; Kolson, Dennis; Mehta, Parth; Kessler, Sudha; Lowenthal, Elizabeth; Monokwane, Baphaleng; Anabwani, Gabriel; Bisson, Gregory P.
Abstract : Background: Seizures are common among patients with HIV/AIDS in the developing world and are associated with significant morbidity and mortality. Early treatment with combination antiretroviral therapy (cART) may reduce this risk by decreasing rates of central nervous system infections and HIV encephalopathy. Methods: A case–control study of new-onset epilepsy among children aged 0–18 years with perinatally acquired HIV/AIDS followed in Gaborone, Botswana, during the period 2003–2009 was conducted. Children with epilepsy were identified and compared with age- and sex-matched controls without epilepsy with respect to timing of cART initiation. Early treatment was defined as treatment with cART before the age of 12 months, at a CD4% of greater than 25 in children aged 1–5 years, or at an absolute CD4 count of >350 cell per cubic millimeter in children aged 5 years and older. Results: We identified 29 cases of new-onset epilepsy and 58 age- and sex-matched controls. The most common identified etiologies for epilepsy were central nervous system infections and direct HIV neurotoxicity. Only 8 (28%) of the children who developed epilepsy received early treatment compared with 31 (53%) controls (odds ratio: 0.36, 95% confidence interval: 0.14 to 0.92, P = 0.03). This effect was primarily driven by differences in rates of epilepsy among children who initiated treatment with cART between the ages of 1 and 5 years (11% vs. 53%, odds ratio: 0.11, 95% confidence interval: 0.01 to 1.1, P = 0.06). Conclusions: Earlier initiation of cART may be protective against epilepsy in children with HIV.